Scaling up experiential learning tools for sustainable water governance in India: Outreach event report - Carrillo, Lucia; Meinzen-Dick, Ruth S.; Priyadarshini, Pratiti; Sanil, Richu (International Food Policy Research Institute, 2023)
This report provides an overview of discussions that transpired during the outreach event titled "Scaling up Experiential Learning Tools for Sustainable Water Governance in India." Held in New Delhi, India, on October 18th, 2023, this event served as a platform for renowned experts, practitioners, and members of the donor community to engage in conversations concerning the complex landscape of water governance in India. The primary focus of this event was to address the challenges and seizing opportunities in this critical domain while emphasizing the need to extend sustainable water management initiatives beyond the current project areas.